Contribution of different frass fertilizer products on enhanced growth, yield and nutrient quality of Broccoli [Brassica oleracea] - Kagehi, Noella; Beesigamukama, Dennis; Tanga, Chrysantus M.; Ngugi, Mathew P.; Subramanian, Sevgan; Khamis, Fathiya M. (Frontiers in Plant Science, 2025)
Vegetables are crucial for food security and income, but in developing countries their production is hindered by low soil fertility. Although the insect frass fertilizer is a potential solution, its use is constrained by limited product choices. Unlike conventional fertilizers, which are available in different forms, the insect frass fertilizer is mostly available in solid form. Here, we evaluated the effects of different black soldier fly frass fertilizer (BSFFF) products on broccoli [Brassica oleracea] growth, yield, and nutritional profiles. Solid, liquid BSFFF, chitin-fortified solid BSFFF, chitin-fortified liquid BSFFF, and commercial organic fertilizer (Safi) were applied at rates equivalent to 250 kg N ha-1 for two cropping seasons. The control treatment consisted of unfertilized soil. Results showed that solid and chitin-fortified solid BSFFF products significantly increased broccoli leaf growth and chlorophyll concentration by 54% and 11%, respectively, compared to the other BSFFF products. Soils amended with BSFFF products produced broccoli with higher number of heads (28 – 158%), fresh yield (26 – 138%), dry yield (17 – 60%), and aboveground biomass (7 – 117%) compared to Safi and control treatments. Broccoli grown in soil amended with BSFFF had higher nitrogen (84%), phosphorus (93%), potassium (51%) uptake, and agronomic use efficiency (4.6-fold) as compared to Safi and the control. Additionally, the application liquid BSFFF produced broccoli heads with higher levels of crude fat (61%), carbohydrates (16%), and calcium (38%) compared to other BSFFF products. Conversely, broccoli grown using chitin-fortified BSFFF exhibited the highest levels of crude protein, potassium, crush ash, and phosphorus. The net income and gross margin achieved with BSFFF treatments were 19 – 26-fold and 29 – 63-fold higher than values obtained Safi, respectively, with higher profitability achieved using chitin-fortified BSFFF formulations. These findings demonstrate the efficacy of different BSFFF formulations in supporting circular economy for safe vegetable production, and improved food and nutrition security.